MODERN IMMUNOTHERAPY OF ADULT B-LINEAGE ACUTE LYMPHOBLASTIC LEUKEMIA WITH MONOCLONAL ANTIBODIES AND CHIMERIC ANTIGEN RECEPTOR MODIFIED T CELLS - Elena Maino; Anna Maria Scattolin; Piera Viero; Rosaria Sancetta; Anna Pascarella; Michele Vespignani; Renato Bassan (Mediterranean Journal of Hematology and Infectious Diseases)
The introduction of newer cytotoxic monoclonal antibodies and the chimeric antigen receptor-modified T-cells is opening a new age in the management of B-lineage adult acute lymphoblastic leukemia. This therapeutic change must be very positively acknowledged because of the limits of intensive chemotherapy programs and allogeneic stem cell transplantation. With these traditional therapeutic tools in fact cure can be achieve in only 40-50% of the patients, with higher failure rates in the elderly, in those with post-induction persistence of minimal residual disease and especially in refractory/relapsed disease. The place of the novel immunotherapeutics in improving the outcome of adult patients with B-lineage acute lymphoblastic leukemia is reviewed.